Home parasternal electromyography tracks patient-reported and physiological measures of recovery from severe COPD exacerbation. Issue 2 (26th April 2021) - D'Cruz, Rebecca Francesca; Suh, Eui-Sik; Kaltsakas, Georgios; Dewar, Amy; Shah, Neeraj Mukesh; Priori, Rita; Douiri, Abdel; Rose, Louise; Hart, Nicholas; Murphy, Patrick Brian
Exacerbations of COPD remain a leading cause of emergency hospitalisations worldwide, and up to 28% of patients are readmitted within 30 days of discharge [1]. Recent analyses of more than 2.3 million COPD hospitalisations highlight the dynamic and time-dependent nature of readmission risk, which peaks within the first 72 h of discharge [2, 3]. Effective readmission prevention strategies remain elusive and recognition of re-exacerbations beyond daily symptom variability is challenging for both patients and clinicians. Promotion of transitional care services and 30-day readmission penalties implemented by policymakers worldwide have had limited impact [4]. Telemonitoring strategies incorporating symptom and vital observation monitoring (peripheral oxygen saturation ( S pO2 ), heart rate, respiratory frequency) have consistently failed to demonstrate beneficial effects on hospitalisation risk [5]. Objective physiological monitoring has been explored using the forced oscillation technique. However, this also failed to prolong time to first hospitalisation [6]. Physiological phenotyping using daily home-based assessments reveals early improvement in load–capacity–drive imbalance following #AECOPD and feasibility of home parasternal electromyography measurement, which tracks symptoms, health status and spirometry https://bit.ly/3o6I0Ty